Analisis Pemberian Enenrgi Gel pada Penggemar Bersepeda Club Gotong Royong Waru Sidoarjo - Dea Wahyoni, Azriel; Anggraini , Febiana Safira; Candra Dewi, Ratna (Universitas Hamzanwadi, 2024)
Energy gels are a quick and easily digestible source of energy for cyclists. The content contained in gel energy is that it contains a concentrated source of carbohydrates, which are active ingredients that provide energy. The purpose of this study was to determine the perception and effects of gel energy consumption on cyclists at Club Gotong Royong Waru Sidoarjo. This research method is descriptive quantitative. The subjects used in this study consisted of 15 gel energy consumers. Instruments and data collection techniques in this study were using a questionnaire and several interviews conducted on filling out the questionnaire. The results showed that there was an average difference between the results of giving gel energy at posttest and posttest, which means that there is an effect of using gel energy in improving performance during cycling. Based on the “Paired Samples Test” output table, the Sig. (2-tailed) is 0.01 < 0.05, then HO is rejected and Ha is accepted. So it can be concluded that there is an average difference between the results of the posttest and the posttest, which means that there is an effect of using gel energy on the pulse rate of cyclists from the gotng royong Waru Sidoarjo club.